Engineering of a Mo/SixNy Diffusion Barrier to Reduce the Formation of MoS2 in Cu2ZnSnS4 Thin Film Solar Cells - Zhengfei Wei (ACS Applied Energy Materials, 2018)
The optimisation of the interface between back contact and absorber is one of the main challenges to improve the electrical behaviour and further enhance the efficiencies of Cu2ZnSn(S,Se)4 (CZTS(e)) solar cell devices. In this work, Mo/SixNy thin films with various film thicknesses were introduced as an interfacial layer to explore its influence on opto-electronic properties of the pure sulphide CZTS thin film solar cells. The SixNy was deposited through plasma enhanced chemical vapour deposition (PECVD). The film thickness and stress of the Mo/SixNy films were controlled to improve the adhesion of the CZTS layer and reduce the chances of cracking the deposited films. Energy dispersive X-Ray spectroscopy (EDS) mapping measurements performed directly on the cross-section of Mo/SixNy/CZTS/Mo films indicate that the SixNy intermediate layer can effectively inhibit the formation of a highly resistive MoS2 layer and decomposition of CZTS at the CZTS/Molybdenum (Mo) interface region. A reduced efficiency was obtained with a SixNy modified back contact compared with the devices without this layer. This could be due to the increased recombination and poor hole extraction stemming from the very low valance band maximum of SixNy obtained from ultraviolet photoelectron spectroscopy (UPS) measurements. Temperature dependent current density-voltage (T-JV) and temperature dependent transient photovoltage (T-TPV) measurements were used to uncover insights into the internal recombination dynamics of the charge carriers.